Experiences of perioperative care among ethnically diverse older adult patients: An integrative review. Issue 6 (December 2022) - Bonus, Charmaine G.; Northall, Tiffany; Hatcher, Deborah; Montayre, Jed
Abstract: Background: Older people from Culturally and Linguistically Diverse (CALD) backgrounds are increasingly admitted to hospital for acute care reasons, such as surgical procedures. However, there is limited evidence on the perioperative (surgical) experiences and needs of ethnically diverse older adults. Aim: To synthesise evidence about the perioperative experiences of older adults from ethnically diverse backgrounds. Methods: An integrative review methodology. Findings: Eighteen articles were included in the review. Three main themes emerged from the review of the literature; (i) Culturally related factors as drivers to decision-making preoperatively; (ii) Providing culturally responsive and appropriate perioperative information; and (iii) Culturally related considerations for effective self-management postoperatively. Discussion: The perioperative needs of ethnic groups are contextualised or informed by culture, ethnicity and linguistics. These needs are not necessarily exclusive to those of ethnically diverse backgrounds. For example, the perceived need for understandable information to make an informed decision would be considered as an essential aspect of perioperative care for any patient. However, the need for understandable information and the complexities of effective communication in perioperative settings are compounded by nuances of culture and language. Conclusion: There needs to be culturally appropriate perioperative processes of care, which build on the standard practice. While patient needs are addressed by universal processes, there is a need to expand and utilise approaches that are culturally and linguistically responsive to older adult patients and their family caregivers. The availability of appropriate mechanisms to engage with healthcare in a culturally meaningful way has the potential to reduce health inequities and improve patient experience.